'Communication, that is the key': a qualitative investigation of how essential workers with COVID-19 responded to public health information. Issue 7 (7th July 2022) - Roe, Mark; Buggy, Conor; Ingram, Carolyn; Codd, Mary; Buckley, Claire; Archibald, Mary; Rachwal, Natalie; Downey, Vicky; Chen, Yanbing; Sripaiboonkij, Penpatra; Drummond, Anne; Alvarez, Elizabeth; et al.
Abstract : Objectives: To understand how essential workers with confirmed infections responded to information on COVID-19. Design: Qualitative analysis of semistructured interviews conducted in collaboration with the national contact tracing management programme in Ireland. Setting: Semistructured interviews conducted via telephone and Zoom Meetings. Participants: 18 people in Ireland with laboratory confirmed SARS-CoV-2 infections using real-time PCR testing of oropharyngeal and nasopharyngeal swabs. All individuals were identified as part of workplace outbreaks defined as ≥2 individuals with epidemiologically linked infections. Results: A total of four high-order themes were identified: (1) accessing essential information early, (2) responses to emerging 'infodemic', (3) barriers to ongoing engagement and (4) communication strategies. Thirteen lower order or subthemes were identified and agreed on by the researchers. Conclusions: Our findings provide insights into how people infected with COVID-19 sought and processed related health information throughout the pandemic. We describe strategies used to navigate excessive and incomplete information and how perceptions of information providers evolve overtime. These results can inform future communication strategies on COVID-19.